METASTASIS TO THE BREAST FROM EXTRAMAMMARY MALIGNANCIES: MAMMOGRAPHIC FEATURES - MUTTARAK, Malai; NIMMONRAT, Angsana; POJCHAMARNWIPUTH, uwalee; CHAIWUN, Benjaporn (The ASEAN Journal of Radiology, 2023)
Metastatic tumors to the breast from extramammary malignancies are unusual. We present 3 cases of such lesions. Two cases were in females with one primary each from the ovary and lung, and one in a male with primary lung carcinoma. The incidence, pathology and radiographic findings of such metastatic lesions are reviewed.